2006
DOI: 10.1161/01.hyp.0000216634.73504.7d
|View full text |Cite
|
Sign up to set email alerts
|

Office and Ambulatory Blood Pressure Are Independently Associated With Albuminuria in Older Subjects With Type 2 Diabetes

Abstract: Abstract-Blood pressure strongly predicts microalbuminuria and later progression to renal failure in people with diabetes.Ambulatory blood pressure monitoring seems to be superior to office blood pressure in predicting progression to microalbuminuria in type 1 diabetes. The associations of ambulatory blood pressure with office blood pressure and microalbuminuria in type 2 diabetes remain unclear. We studied the association of office blood pressure taken with an automated device and ambulatory blood pressure wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 45 publications
(36 reference statements)
5
20
0
Order By: Relevance
“…371 In older patients with type 2 diabetes mellitus, both high-office SBP and high-awake ambulatory SBP independently predict albuminuria. 372 …”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…371 In older patients with type 2 diabetes mellitus, both high-office SBP and high-awake ambulatory SBP independently predict albuminuria. 372 …”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Moran et al found that office and 24 h systolic AMBP were independently associated with albuminuria in elderly type 2 diabetic patients [4]; however in the longitudinal study mentioned above [9], ambulatory PP predicted progression of albuminuria above and beyond office BP. In the present study, none of the office BP values had any significant predictive value for the progression of nephropathy, whereas 24 h systolic AMBP and PP values were strong predictors of nephropathy progression in type 2 diabetic patients.…”
Section: Discussionmentioning
confidence: 93%
“…In particular, focus has been directed towards a blunted nocturnal BP reduction ('non-dipping'), a pattern that has been consistently associated with diabetic vascular complications in previous studies [1,[10][11][12][13][14][15][16][17]35]. In a 3 year follow-up of the same elderly type 2 diabetic patients mentioned above [4,9], the investigators found that patients with a reversed diurnal BP rhythm (nocturnal BP 'risers') had an increased risk of nephropathy progression compared with patients with a normal reduction in BP during nighttime ('dippers'), whereas patients with a reduced nocturnal BP decline ('non-dippers') had an intermediate risk of progression [19]. Nocturnal BP rising was an independent predictor of albuminuria progression in the multivariate analysis, whereas non-dipping did not independently predict albuminuria progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 A series of reports dealing with diabetic patients have also shown a close correlation between ambulatory BP and diabetic complications. 4,5 Evidences are available for the entire cardiorenal continuum of diabetic damage from the prediction of microalbuminuria by early changes in nocturnal BP in type 1 patients 6 to the effect of a riser pattern on mortality in patients with type 2 diabetes. 7 Nevertheless, information about the ABPM characteristics of large cohorts of diabetic hypertensives attending primary care centers is scarce.…”
Section: Introductionmentioning
confidence: 99%